Spiritual Leadership and Emotional Intelligence of Principal and Teachers at Serba Bakti Suryalaya Islamic Boarding School Foundation - Bela Elqaweliya; Djam’an Satori; Diding Nurdin; Eka Prihatin; Nuphanudin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity provides understanding and implementation of spiritual leadership and emotional intelligence to school Principal and Teachers. This work aims to provide solutions to the current leadership crisis due to the deterioration of current human values. The service activities conducted in the form of workshops, by discussing the spiritual leadership of teachers in the character building of students and the spiritual leadership process of teachers in character building. In addition, the workshop also discussed how emotional intelligence supports principals and teachers to manage stress, make the right decisions, and resolve conflicts in a positive approach. Some of the activities conducted during the workshop included the delivery of material from resource persons in the hall and activities in the mosque such as khataman, manakib, and dhikr. After the workshop, participants learned more about spiritual leadership and emotional intelligence. The service activity took place for one day and gained appreciation from the participants of the workshop.